Case-Based Knowledge and Planning - Itzhak Gilboa; David Schmeidler (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1995)
"Case-Based Decision Theory" is a theory of decision making under uncertainty, suggesting that people tend to choose acts that performed well in similar cases they recall. The theory has been developed from a decision-/game-/economic-theoretical point of view, as a potential alternative to expected utility theory. In this paper we attempt to re-consider CBDT as a theory of knowledge representation and of planning, to contrast it with the rule-based approach, and to study its implications regarding the process of induction.
Keywords: 330